2016
DOI: 10.1002/brb3.605
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a Norwegian adaption of the Barratt Impulsiveness Scale‐11 in a sample of Parkinson patients, headache patients, and controls

Abstract: ObjectiveTo assess the psychometric properties of a Norwegian translation of the Barratt Impulsiveness Scale (BIS‐11) for use in populations of headache, Parkinson's disease (PD), and healthy controls.Materials and MethodsThe BIS‐11 was forward and backward translated by native speakers of both Norwegian and English to give Norwegian BIS‐11 (Nor‐BIS‐11). A convenience sample (110 subjects) of healthy controls (47), PD patients (43), and chronic headache patients (20) (the latter two recruited from a Neurology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…Internal consistency of the BIS-11 total score has been repeatedly reported as acceptable (Lindstrom, Wyller, Halvorsen, Hartberg, & Lundqvist, 2017;Patton et al, 1995;Reise, Moore, Sabb, Brown, & London, 2013;Stanford et al, 2009).…”
Section: Clinical Measuresmentioning
confidence: 95%
See 1 more Smart Citation
“…Internal consistency of the BIS-11 total score has been repeatedly reported as acceptable (Lindstrom, Wyller, Halvorsen, Hartberg, & Lundqvist, 2017;Patton et al, 1995;Reise, Moore, Sabb, Brown, & London, 2013;Stanford et al, 2009).…”
Section: Clinical Measuresmentioning
confidence: 95%
“…Hence, the total score ranges from 30 to 120, with higher scores reflecting higher levels of impulsivity. Internal consistency of the BIS‐11 total score has been repeatedly reported as acceptable (Lindstrom, Wyller, Halvorsen, Hartberg, & Lundqvist, 2017; Patton et al., 1995; Reise, Moore, Sabb, Brown, & London, 2013; Stanford et al., 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Instead, when examining other impulsivity traits there is still some concern regarding whether PD patients and the healthy controls (HCs) are characterized by different levels, since there are conflicting results. For instance, when comparing those two groups on the Barratt Impulsiveness Scale‐11 th version (BIS‐11; Patton, Stanford, & Barratt, ), some studies found that they did not score significantly different (e.g., Fonoff et al ., ; Lindstrøm, Wyller, Halvorsen, Hartberg, & Lundqvist, ), whereas others reported that PD patients scored higher than people without PD (e.g., Christenson et al ., ; Nombela, Rittman, Robbins, & Rowe, ; Piray et al ., ). Moreover, one study reported that PD patients who also reported ICDs were as impulsive as the HCs on the BIS‐11, whereas PD patients without ICDs were less impulsive (Voon et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The Barratt Impulsiveness Scale-11 (BIS-11) assesses overall impulsivity and three subscales -attention, motor and non-planning. Higher scores indicate greater impulsivity [22]. The Dutch version of the BIS-11 has been validated in normal and clinical samples [23].…”
Section: Methodsmentioning
confidence: 99%